THE INFLUENCE OF INTERNET ADDICTION ON ANXIETY INDICATORS IN MEDICAL UNIVERSITY STUDENTS - Evgeny V. Derevyannich; Natalia A. Balashova; Roman A. Yaskevich; Olga L. Moskalenko (Russian Journal of Education and Psychology, 2022)
The purpose of the study. To study the influence of Internet addiction on anxiety indicators in medical university students.